O modelo da sala de aula invertida para a aprendizagem conceitual em termodinâmica básica - Pacheco, Janaina Bezerra (2022)
The present work presents a study whose object is the teaching and learning processes about conceptual learning in basic thermodynamics; temperature, heat and change of state. The research subjects were 2nd year high school students from a full-time public school in the city of Parintins. This work aimed to develop a booklet on the subject in question using the model of the inverted classroom, the SAI. The research methodology had a qualitative approach, since the students' responses were investigated in the pre-test, during the experimental activities in the classroom, in the transcripts of student reports and in the post-test. A bibliographic review was carried out on conceptual learning, the scientific concept as a notorious learning difficulty in physics, and the model of the Inverted Classroom (IS). We designed the educational product in the form of a booklet to help the teacher with regard to learning the basic concepts of thermodynamics. As a result, we found evidence that there was conceptual learning of the highlighted subjects. It is noteworthy that the entire development of this work, as well as the implementation of the methodological steps took place in the full context of the Covid-19 pandemic.